2020
DOI: 10.1186/s13018-020-01594-w
|View full text |Cite
|
Sign up to set email alerts
|

Matching actual treatment with patient administration-route-preference improves analgesic response among acute low back pain patients—a randomized prospective trial

Abstract: Background: Accommodating a patient's treatment preference has been reported to promote greater responsiveness and better clinical outcomes. The effect of administration route preference (ARP) on the individual analgesic response has not been extensively examined to date. This study aimed to investigate whether ARPmatched treatment, i.e., individualized intramuscular (IM) or oral (PO) analgesic administration according to patient choice, would increase the analgesic effect. Methods: In this prospective randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…If the safety and efficacy of two injections were equivalent, the consideration of patient preference and costs would ensure optimal treatment adherence and ultimately patient experience and satisfaction [34]. Shani et al [35]. found that matching the route of administration of analgesia to patients' preference in the treatment of acute low back pain resulted in greater pain reduction as compared to patients who received analgesia through the undesired route.…”
Section: Discussionmentioning
confidence: 99%
“…If the safety and efficacy of two injections were equivalent, the consideration of patient preference and costs would ensure optimal treatment adherence and ultimately patient experience and satisfaction [34]. Shani et al [35]. found that matching the route of administration of analgesia to patients' preference in the treatment of acute low back pain resulted in greater pain reduction as compared to patients who received analgesia through the undesired route.…”
Section: Discussionmentioning
confidence: 99%